Interaction analysis of FTO and IRX3 genes with obesity and related metabolic disorders in an admixed Latin American population: a possible risk increases of body weight excess (Colombia Medica, 2022)
Background:Fat Mass and Obesity-related (FTO) has been one of the genes consistently related to common obesity. Single nucleotide polymorphisms (SNPs) in FTO have been linked with the IRX3 gene.Aim:This study was designed by testing the hypothesis that: i) common SNPs in FTO and IRX3 are associated with obesity and related disorders; ii) there is significant linkage disequilibrium between both genes.Methods:A cross-sectional study was carried out on the Colombian Caribbean Coast. Anthropometric and biochemical variables were measured, and obesity and metabolic disorders were diagnosed. Four SNPs were genotyped: 3 at FTO locus (rs17817449, rs8050136, rs9939609) and one at IRX3 locus (rs3751723). LD between these SNPs was estimated. A logistic regression model was applied to estimate associations.Results:A total of 792 subjects were included. FTO and IRX3 were not in LD (D’≤ 0.03; R2≤ 0.03). TT genotype (rs9939609) was found to be associated with waist circumference (p= 0.04; adj-p=0.01), and IRX3 SNP with Body Weight Excess (BWE) (OR= 1.06, adj-p= 0.03). One FTO-IRX3 haplotype was associated with BWE (G-A-A-T, rs17817449-rs8050136-rs9939609-rs3751723; OR= 0.67, p= 0.04). The statistical significance of these relations continued after admixture adjustment for a three-hybrid population (p= 0.03).Conclusions:FTO was related to waist circumference, and IRX3 was associated with BWE in Latin American adults. This relation remained statistically significant after performing an adjustment for sex, age, and genetic ancestry. Despite these genes not being in LD, findings of a haplotype involving FTO-IRX3 suggest a gene-gene interaction associated with an increased risk of BWE.